Antimicrobial activity of the marine actinomycetes - Gulve, R M; Deshmukh, A M (International Multidisciplinary Research Journal, 2012)
Antibacterial activity of 107 marine actinomycetes isolated form near sea shore sediment and seawater from Konkan coast of Maharashtra was studied. A total 107 actinomycetes were subjected to primary screening by perpendicular streak method against various test microorganisms. Among 107 actinomycetes 22,14,34,14,07,52,27 and 6 number of actinomycetal isolates were antagonistic against Bacillus subtilis, Staphylococcus aureus, Proteus vulgaris ,Escherichia coli, Klebsiella aerogenes , Pseudomonas aeruginosa.,Candida albicans and Aspergillus. niger respectively. Out of 107 actinomycetal isolates 13 isolates showing maximum antagonistic activities that were subjected for the secondary screening by agar well method. Finally 0 5 isolates were selected for further study on the basis of maximum zone of inhibition and broad spectrum activity. Selected 05 isolates were inoculated in glucose soybean broth 7 days at 300C and antibacterial substances were extracted with ethyl acetate.T L C of the ethyl acetate extract was carried out using N butanol : acetic acid : water ( 4:1:5 ) as a solvent system. Spots were observed under UV light and in iodine chamber. Bioautograhy of ethyl acetate extract of selected 05 isolates were carried using test organisms B. subtilus and P. vulgaris. Inhibition zones were observed and they were associated with the purple spots at the chromatograms as detected under UV light. This may indicate the same compound was responsible for the antibacterial activity of the actinomycetes.Finaly one potent actinomycetal isolate (GA-22) was selected and it’s morphological, cultural, physiological and biochemical characters was studied. It was found that biochemically GA-22 was very active marine actinomycetes it was able to produce variety of enzymes and utilize number of sugars.